Short cylindrical electron bunch dynamics and wake fields` excitation in plasma with the external magnetic field - Shcherbinin, M.A.; Anisimov, I.O. (Вопросы атомной науки и техники, 2015)
Dynamics of the non-relativistic cylindrical electron bunch injected into the homogeneous plasma along the external magnetic field was studied using computer simulation via PIC method. The initial bunch length was equal to the wake wave length of the background plasmas. The simulation results are compared with the case without magnetic field. It is shown that strong external magnetic field suppresses the radial bunch defocusing but moves to the further longitudinal expansion of the bunch. As a result the area of the wake wave excitation grows substantially. Periodicity of the background plasma current is determined by the excited wake wave.